2023
DOI: 10.3389/fpubh.2023.1238144
|View full text |Cite
|
Sign up to set email alerts
|

Stress experiences of healthcare assistants in family practice at the onset of the COVID-19 pandemic: a mixed methods study

Hanna Schrader,
Jessica Ruck,
Gábor Borgulya
et al.

Abstract: BackgroundAt the beginning of the pandemic in 2020, healthcare assistants in general practices were confronted with numerous new challenges. The aim of the study was to investigate the stress factors of healthcare assistants in March/April 2020 as well as in the further course of the pandemic in 2020.MethodsFrom August to December 2020, 6,300 randomly selected healthcare assistants in four German states were invited to participate in the study. We performed a mixed methods design using semi-structured telephon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…These identified differences in the AVEM dimensions can be explained by the different areas of work of the professional groups. Practice assistants are probably confronted with more dissatisfied patients than practice owners [38] and, therefore, receive less recognition for their work. Thus, lower scores for "experience of success at work" and "satisfaction with life" in this group are not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…These identified differences in the AVEM dimensions can be explained by the different areas of work of the professional groups. Practice assistants are probably confronted with more dissatisfied patients than practice owners [38] and, therefore, receive less recognition for their work. Thus, lower scores for "experience of success at work" and "satisfaction with life" in this group are not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The identified contextual challenges in this study are similar to prior studies; challenges include staff shortages as a result of infections and subsequent sick leave [ 13 ], the availability of PPE including medical masks [ 14 ], and the frequently changing IPC requirements and regulations during the pandemic [ 8 , 21 , 36 ]. The development and implementation of supportive policies, surveillance and reporting system activation (e.g., dashboards), availability of PPE, staff training, and workforce augmentation have been recommended to enhance pandemic preparedness of primary care [ 18 , 37 ]. In addition, previous qualitative findings have demonstrated an experienced lack of clarity and ambiguity in the guidelines during the pandemic [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPs experienced high workload and work pressure during the pandemic, due to the overwhelming COVID-19 care and administrative burdens [ 3 , 15 17 ]. Moreover, medical assistants experienced high feelings of psychological burden during the first wave of the pandemic [ 18 ]. Next to these contextual challenges related to the pandemic, previous studies have identified practice and system factors to hinder IPC during the pandemic, such as inadequate GP practice building layout, limited IPC resources and materials, infrastructure constraints, and rapidly changing guidelines [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%